2007
DOI: 10.1016/j.dsr.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

A taste of the deep-sea: The roles of gustatory and tactile searching behaviour in the grenadier fish Coryphaenoides armatus

Abstract: The deep-sea grenadier fishes (Coryphaenoides spp.) are among the dominant predators and scavengers in the ocean basins that cover much of Earth's surface. Baited camera experiments were used to study the behaviour of these fishes. Despite the apparent advantages of rapidly consuming food, grenadiers attracted to bait spend a large proportion of their time in prolonged periods of non-feeding activity. Video analysis revealed that fish often adopted a head-down swimming attitude (mean of 21.3 o between the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In the adult stages of life, certain macrourid species likely rely on olfaction and mechanoreception to find food sources and possibly use vision to find mates or, to a lesser extent, food (Wagner 2002(Wagner , 2003. Bailey et al (2007) suggested that grenadiers use olfaction to locate food sources from a distance, but rely on gustation and mechanoreception at close ranges to the source. It is possible that vision plays a minor role in the feeding ecology of adult C. acrolepis.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult stages of life, certain macrourid species likely rely on olfaction and mechanoreception to find food sources and possibly use vision to find mates or, to a lesser extent, food (Wagner 2002(Wagner , 2003. Bailey et al (2007) suggested that grenadiers use olfaction to locate food sources from a distance, but rely on gustation and mechanoreception at close ranges to the source. It is possible that vision plays a minor role in the feeding ecology of adult C. acrolepis.…”
Section: Discussionmentioning
confidence: 99%
“…In the fish having external taste buds, an irreversible ablation of olfactory receptors causes only a transient loss of sensitivity to feed signal sub stances dissolved in water; 2-3 months later, the fish restore the ability to search for remote sources of food chemical signals (Kasumyan and Marusov, 2002Marusov and Kasumyan, 2010). First and foremost, the presence of external taste buds is characteristic of nocturnal fish and fish inhab iting benthic and near benthic biotopes and feeding mainly on benthic organisms (Kapoor et al, 1975;Ovalle and Shinn, 1977;Atema, 1980;Pevzner, 1981Pevzner, , 1985Devitsina and Kazhlaev, 1992;Lombarte and Aquirre, 1997;Harvey and Batty, 2002;Bailey et al, 2007). The more pronounced a benthic life habit and benthic feeding, the larger fish body areas are covered with external taste buds and the higher is their total number (Gomahr et al, 1992).…”
Section: Discussionmentioning
confidence: 95%
“…The inclusion of data for chimaeroids into pre-existing large, comparative elasmobranch datasets such as those that exist for eye size and the morphology of the olfactory system (Schluessel et al 2008) and the inner ear (Evangelista et al 2010) may prove particularly fruitful and would allow sensory system ecomorphology to be assessed within a phylogenetic context. It may also be possible to combine anatomical information with behavioural observations and experiments conducted using landers as has been done to investigate the role of taste and tactile senses in search behaviour in deep-sea fishes (Bailey et al 2007). …”
Section: Discussionmentioning
confidence: 99%